Avaliação do carregamento e do comportamento térmico de transformadores de distribuição através da aplicação do método de estimação de estados - Silva, Émerson Rafael da (2019)
The need to know the real state of operation of the Electrical Systems is one of the most important aspects in the scope of Smart Grids. To accomplish this, obtaining real-time data from a comprehensive monitoring model is necessary since these data provide an accurate diagnosis of the operation. This acquisition of data in an ideal scenario requires a large scale of electric magnitude meters along the network. In very large distribution networks, this large-scale monitoring becomes practically impossible, and in this context, the State Estimator appears, which, as its name suggests, raises estimates of network states at points where there are no measurements. For the operation of the algorithms, the State Estimator needs measurements along the branches, in which an optimized distribution of the meters allows the reduction of uncertainties and associated errors in the estimation itself. In addition, better allocation of the meters increases bus observability of the buses. The knowledge of the actual point of operation of the Electrical System equipment, in this way, is of great importance and the state estimator can be an auxiliary tool to achieve this goal. One of the most important equipment of the system is the Distribution Transformer, which is usually the equipment that most suffers in times of critical demand. The operation of these equipment is correlated to the lifetime of the insulation, constituted, in general lines, by paper and oil. The durability of the transformer insulation is related to thermal supportability and the equivalent aging factor. Correlating, the temperature in the windings and the insulating oil is proportional to the transformer load, which can be obtained by the State Estimator. Thus, this work highlights a study of an application of the State Estimation Method in a Distribution System to determine the load of the transformers, and then, to verify its thermal performance during the 24 hours of a day. The thermal model was based on a normalized equation and it is widely accepted in the literature. In short, the use of the two studies can be interesting from the point of view of the system operation, and consequently, planning. The State Estimator, therefore, provides the precise state of operation and closer to the real, while the Thermal Model study presents the current condition of the transformers for the traced scenario. As case studies, firstly, models will be validated and subsequently applied in a distribution network. For this, two computational tools were used: one for the scenario application and the State Estimator, and another for the development of the Thermal Model equation.